Stable isotope composition of cocoa beans of different geographical origin. (6th September 2016) - Perini, Matteo; Bontempo, Luana; Ziller, Luca; Barbero, Alice; Caligiani, Augusta; Camin, Federica
Abstract : The isotopic profile ( δ 13 C, δ 15 N, δ 18 O, δ 2 H, δ 34 S) was used to characterise a wide selection of cocoa beans from different renowned production areas (Africa, Asia, Central and South America). The factors most influencing the isotopic signatures of cocoa beans were climate and altitude for δ 13 C and the isotopic composition of precipitation water for δ 18 O and δ 2 H, whereas δ 15 N and δ 34 S were primarily affected by geology and fertilisation practises. Multi‐isotopic analysis was shown to be sufficiently effective in determining the geographical origin of cocoa beans, and combining it with Canonical Discriminant Analysis led to more than 80% of samples being correctly reclassified. Copyright © 2016 John Wiley & Sons, Ltd.